Developing A Pictionary Game-Based Assessment on Vocabulary Mastery for Junior High School Students - Putri, Siti Novia Ade; Wahyuni, Sri (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study focuses on developing a Pictionary game-based assessment tool to enhance vocabulary mastery for junior high school students. The research employs the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to create an interactive and effective assessment method that integrates visual elements to evaluate students' vocabulary knowledge. The Pictionary game, involving drawing and guessing words, is used as an engaging strategy to measure students’ vocabulary retention and understanding in real-world contexts. Findings indicate that although the game offers an enjoyable learning experience, improvements are needed to increase the validity and reliability of the assessment tool. Quantitative data, collected through students' performance on multiple-choice questions, showed that only 10 out of 25 questions met the validity criteria. Additionally, qualitative data, including feedback from teachers and students, revealed that the game's structure significantly impacted students' vocabulary retention and engagement. The study concludes that Pictionary-based assessments can be an effective tool for vocabulary acquisition, but further refinement is required to ensure consistent results and align the questions with students’ abilities.